PENGARUH LABA AKUNTANSI DAN ARUS KAS OPERASI TERHADAP RETURN SAHAM (STUDI PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2019 – 2023) - Renato Mewengkang; Cory Tobing (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis, 2025)
The capital market serves as a platform for people to invest in financial instruments such as stocks. Stock returns attract investors. While accounting profit and operating cash flow theoretically influence stock returns, in practice, there is an inconsistency between this theory and the company's financial statements. The purpose of this study was to examine the effect of accounting profit and operating cash flow on stock returns in food and beverage companies listed on the Indonesia Stock Exchange for the 2019-2023 period. The data source used was secondary data, namely the companies' annual financial reports. A sample of 11 companies was used, with a total of 55 data points. The analytical methods employed were classical assumption testing, multiple linear regression, and hypothesis testing. The results showed that accounting profit had a significant partial effect on stock returns (b = 0,141; r = 0,000). Operating cash flow had no significant partial effect on stock returns (b =0,000; r = 0,860). Simultaneously, accounting profit and operating cash flow significantly influence stock returns (F-hit =7,511; r = 0,001).